Beyond a Zero-Sum Game: How Does the Impact of COVID-19 Vary by Gender? - Morgan, Rosemary; Baker, Peter; Griffith, Derek M; Klein, Sabra L.; Logie, Carmen H; Mwiine, Amon Ashaba; Scheim, Ayden I; Shapiro, Janna R.; Smith, Julia; Wenham, Clare; White, Alan (Frontiers in Sociology, 2021)
Epidemics and pandemics, like COVID-19, are not gender neutral. Much of the current work on gender, sex, and COVID-19, however, has seemed implicitly or explicitly to be attempting to demonstrate that either men or women have been hardest hit, treating differences between women and men as though it is not important to understand how each group is affected by the virus. This approach often leaves out the effect on gender and sexual minorities entirely. Believing that a more nuanced approach is needed now and for the future, we brought together a group of gender experts to answer the question: how are people of different genders impacted by COVID-19 and why? Individuals working in women’s, men’s, and LGBTQ health and wellbeing wrote sections to lay out the different ways that women, men, and gender and sexual minorities are affected by COVID-19. We demonstrate that there is not one group “most affected,” but that many groups are affected, and we need to move beyond a zero-sum game and engage in ways to mutually identify and support marginalized groups.